Analisis Lingkungan Bisnis PT Adaro Energy, Tbk - Abdurahman Abdurahman; Saladin Ghalib; Maryono Maryono (Universitas Lambung Mangkurat, 2020)
Abdurahman, NIM D2A215001 Analysis of Business Environment PT Adaro Energy, Tbk. Thesis of the Master Program in Business Administration, Post Graduate Program of Lambung Mangkurat University, guided by Saladin Ghalib and Maryono.This study aims to determine the factors of the business environment that are the strengths and opportunities of PT Adaro Energy, Tbk. As well as business environment factors which are weaknesses and threats to PT Adaro Energy, Tbk and what business strategies PT Adaro Energy, Tbk is based on existing environmental conditions.To achieve these objectives this study uses a qualitative approach, type of case study, data collection with interviews, observation and documentation. Data analysis with EFE, IFE and SWOT.Of the many strength factors, the most prominent are business models that are integrated from the mine to electricity, low costs, large resource reserves and long-term contracts.Whereas the environmental factors that pose a threat are fluctuating prices, alternative energy, regulatory uncertainty, carbon emission concerns, and the global economic downturn. While the weaknesses of current production are only supported by one mine, remote mining location, long-term investment and high risk, capital intensive and need special expertise.Based on the grand strategy, the business strategy carried out by PT Adaro Energy is aggressive focusing on developing the domestic market and vertical diversification. This aggressive strategy needs to be maintained in accordance with the results of the general electric model calculation that shows Stability.Keywords: Business Environment, PT Adaro Energy, Tbk